2019
DOI: 10.1111/mmi.14372
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient depletion may trigger the Yersinia pestis OmpR‐EnvZ regulatory system to promote flea‐borne plague transmission

Abstract: The flea's lumen gut is a poorly documented environment where the agent of flea-borne plague, Yersinia pestis, must replicate to produce a transmissible infection. Here, we report that both the acidic pH and osmolarity of the lumen's contents display simple harmonic oscillations with different periods. Since an acidic pH and osmolarity are two of three known stimuli of the OmpR-EnvZ two-component system in bacteria, we investigated the role and function of this Y. pestis system in fleas. By monitoring the in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 69 publications
1
25
0
Order By: Relevance
“…It can regulate transcription in a positive or negative way by binding to consensus sequence elements that occur at different locations in promoter regions [ 54 , 55 , 56 ]. It has been shown that the EnvZ/OmpR system modulates the expression of numerous genes in response to environmental changes such as altered osmolarity, pH and nutrient content [ 57 , 58 , 59 , 60 , 61 , 62 ]. The transcriptional regulator OmpR has been best studied for its role in the inverse osmoregulation of the outer membrane porins OmpC and OmpF in E. coli .…”
Section: Introductionmentioning
confidence: 99%
“…It can regulate transcription in a positive or negative way by binding to consensus sequence elements that occur at different locations in promoter regions [ 54 , 55 , 56 ]. It has been shown that the EnvZ/OmpR system modulates the expression of numerous genes in response to environmental changes such as altered osmolarity, pH and nutrient content [ 57 , 58 , 59 , 60 , 61 , 62 ]. The transcriptional regulator OmpR has been best studied for its role in the inverse osmoregulation of the outer membrane porins OmpC and OmpF in E. coli .…”
Section: Introductionmentioning
confidence: 99%
“…Some fleas, particularly those that feed frequently, such as the cat flea Ctenocephalides felis , excrete undigested and partially digested portions of their blood meal during or soon after feeding [ 7 ]. The midgut pH fluctuates between about 6.5 and 7 at different times after a blood meal, and osmolarity drops from around 500 to 300 mOsm, gradually increasing over the next 24 h to the original value as digestion proceeds [ 8 ]. The flea gut is aerobic, oxygenated by an extensive abdominal trachea system that is maximally active during blood digestion [ 9 ].…”
Section: The Insect Host Environmentmentioning
confidence: 99%
“…If the PhoPQ system is nonfunctional, several other general and acid stress response genes are upregulated in the flea [ 28 ]. As the flea digests and absorbs blood meal elements, the osmolarity of the midgut contents increases [ 8 ], and several Y. pestis genes with osmoadaptive and osmoprotective functions are upregulated [ 25 , 27 , 29 , 74 ]. The stress-sensing alternative sigma factor, RpoE, is also upregulated in the flea [ 25 ].…”
Section: Y Pestis Transmission Factorsmentioning
confidence: 99%
“…Mildly acidic pH (~6.6) and hyperosmolarity (~500 mOsm) of the flea gut milieu are considered to be the stress signals encountered by Y. pestis during insect infection [ 66 , 67 ]. PhoP expression is closely linked to management of these stresses in the flea gut, as demonstrated in comparative transcriptomic studies between a phoP mutant and wild-type strain during flea infection [ 64 ].…”
Section: Biofilm and Flea Colonizationmentioning
confidence: 99%